2018
DOI: 10.3390/w10060678
|View full text |Cite
|
Sign up to set email alerts
|

Constructed Wetlands: A Review on the Role of Radial Oxygen Loss in the Rhizosphere by Macrophytes

Abstract: Constructed wetlands (CWs) are extensively used as an economical and environmentally friendly sewage treatment under ecological engineering technology. Knowledge of the oxygen in the rhizosphere is of primary importance in understanding the function and regulation of microbial communities and macrophytes. Numerous studies on radial oxygen loss (ROL) have greatly elucidated the mechanism of contaminant removal in CWs. The main sources of oxygen in CWs are atmospheric reoxygenation, macrophyte transmission, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 56 publications
1
33
0
1
Order By: Relevance
“…The plants that grow in constructed wetlands have several properties related to the water treatment process that make them an essential component of the design. Macrophytes are the main source of oxygen in CWs through a process that occurs in the root zone, called radial oxygen loss (ROL) [17]. The ROL contributes to the removal of pollutants because it favors an aerobic micro-environment, and waste removal is therefore accelerated, whereas, in anaerobic conditions (the main environment in CWs), there is less pollutant removal.…”
Section: Role Of Macrophytes In Cwsmentioning
confidence: 99%
“…The plants that grow in constructed wetlands have several properties related to the water treatment process that make them an essential component of the design. Macrophytes are the main source of oxygen in CWs through a process that occurs in the root zone, called radial oxygen loss (ROL) [17]. The ROL contributes to the removal of pollutants because it favors an aerobic micro-environment, and waste removal is therefore accelerated, whereas, in anaerobic conditions (the main environment in CWs), there is less pollutant removal.…”
Section: Role Of Macrophytes In Cwsmentioning
confidence: 99%
“…For that, they integrate several components, including the treatment basin, substrate, selected plant species, and a panoply of associated organisms [13,14]. Although there are reports on the microbial dynamics and their association to macrophytes, these studies are mainly focused on bacteria [15][16][17], underestimating other important microbial organisms, such as fungi. Both bacteria and fungi have important roles in the assimilation, transformation, and recycling of chemical constituents present in various wastewaters.…”
Section: Introductionmentioning
confidence: 99%
“…Mesocosms with different vegetation and substrate showed no significant difference (p = 0.234). This indicated that the presence of vegetation favored the release of radial oxygen [27], and this allowed nitrification in the rhizosphere zone. After denitrification processes in the anaerobic area, this last process could only have been present in the mesocosms with no plants, and in minor proportions, since the presence of vegetation under anaerobic conditions also favors carbon exudation from the root, which intensifies the denitrification [28].…”
Section: Concentration and Removal Of Contaminants In Cw Mesocosmsmentioning
confidence: 94%